Early Implanon discontinuation and associated factors among Implanon women users visiting public health facilities, in Kembata zone of Southern Ethiopia: An institution based cross-sectional study - Beyene, Gemechu Nigusie; Assefa, Nega; Mokonnon, Taklu Marama; Ejigu, Habtamu Bekele; Yadeta, Tesfaye Assebe (Frontiers in Global Women's Health, 2022)
Background Contraceptive practice is the basis of fertility and plays a significant role in minimizing maternal morbidity and mortality. Implanon is one of the most effective long-acting contraceptive methods that prevents pregnancy for 3 years. Early Implanon discontinuation can lead to many negative reproductive health consequences. Therefore, this study assessed the magnitude of early Implanon discontinuation among female Implanon users visiting public health facilities to discontinue Implanon in the Kembata zone of southern Ethiopia. Methods An institution-based cross-sectional study design was carried out from 1 March 2020 to 30 March 2020. Simple random sampling techniques were used to select 454 women who had discontinued Implanon. The data were collected using a pretested and structured questionnaire. The collected data were entered into Epi Data version-3.1 and then exported to STATA version-16 for analysis. A descriptive analysis along with bivariate and multivariate regression was performed to identify factors associated with early Implanon discontinuation. Statistical significance was declared at a p < 0.05 along with 95% confidence intervals (CIs). Results In the present study, 438 women were interviewed, which corresponds to a response rate of 96.48%. The magnitude of early Implanon discontinuation was 56.4%, 95%CI (51.6, 61.2). Primary educational status [adjusted odds ratio (AOR) = 2.92, 95%CI (1.56, 5.46)], rural residency [AOR = 1.76, 95%CI (1.06, 2.92)], women with no history of modern contraceptive use [(AOR = 2.14, 95%CI (1.14, 4.03)], those who experienced service dissatisfaction [AOR = 3.05, 95%CI (1.52, 6.12)], women who experienced as Implanon side effect [AOR = 3.36, 95%CI (2.09, 5.42)], and women who were not appointed after insertion [(AOR = 2.17, 95%CI (1.18, 4.79)] have shown an association with early Implanon discontinuation. Conclusion The present study indicated that the magnitude of early Implanon discontinuation was high. Educational level, rural residency, women who experienced side effects, those who experienced service dissatisfaction, women with no history of contraceptive use, and those who missed follow-up appointments were associated with Implanon discontinuation. Family planning service providers should focus on Implanon side effects during pre-insertion counseling. The recommended intervention is to recognize modifiable factors like improving client satisfaction with the service, appointing for follow up after insertion, and providing quality family planning services.